Home bound : Filipino American lives across cultures, communities, and countries - Espiritu, Yen Le, 1963- (Berkeley : University of California Press, 2003)
Filipino Americans, who experience life in the United States as immigrants, colonized nationals, and racial minorities, have been little studied, though they are one of our largest immigrant groups. Based on her in-depth interviews with more than one hundred Filipinos in San Diego, California, Yen Le Espiritu investigates how Filipino women and men are transformed through the experience of migration, and how they in turn remake the social world around them.
Home making -- Leaving home : Filipino migration/return to the United States -- "Positively no Filipinos allowed" : differential inclusion and homelessness -- Mobile homes : lives across borders -- Making home : building communities in a Navy town -- Home, sweet home : work and changing family relations -- "We don't sleep around like white girls do" : the politics of home and location -- "What of the children?" : emerging homes and identities -- Homes, borders, and possibilities.
Includes bibliographical references (pages 223-265) and index.
Print version record.
JSTOR
Keywords: Filipino Americans -- Social conditions; Filipino Americans -- Ethnic identity; Families -- United States; Transnationalism; Racism -- United States; United States -- Relations -- Philippines; Philippines -- Relations -- United States; Américains d'origine philippine -- Conditions sociales; Américains d'origine philippine -- Identité ethnique; Familles -- États-Unis.; Transnationalisme; Racisme -- États-Unis.; SOCIAL SCIENCE -- Sociology -- Marriage & Family; SOCIAL SCIENCE -- Emigration & Immigration; Families; Filipino Americans -- Ethnic identity; Filipino Americans -- Social conditions; Racism; International relations; Transnationalism; Philippines; United States